Regions that work : how cities and suburbs can grow together - Pastor, Manuel, 1956- (Globalization and community, 2000)
Regions That Work provides a history and critique of community-development corporations, a statistical analysis of the poverty-growth relationship in seventy-four metro areas, a detailed study of three regions that have produced superior equity outcomes, and a provocative call for new policies and new politics."A remarkable and timely book. ... Must reading." William Julius Wilson